Detail work at Vishnu Temple in Deogarh - Temples of India Project Team (Jio Institute, 2024)
Detail, Vishnu Temple, Deogarh, Uttar Pradesh, India. Ca. early 6th century. Image courtesy: Prof. Chedha Tingsanchali.